STRATEGI AMERIKA SERIKAT MENGHADAPI PEMBENTUKAN ASIAN INFRASTRUCTURE INVESTMENT BANK OLEH TIONGKOK THE U.S STRATEGY TO ENCOUNTER THE ESTABLISHMENT OF ASIAN INFRASTRUCTURE INVESTMENT BANK BY CHINA - Presya Ramadhan (HI 16 UMY 128, 2016)
*128 This article aims to analyze the US strategy to encounter the establishment of Asian Infrastructure Investment Bank (AIIB) by China. Tha author argues that US use the instrument to balance of China influence in Aisa-Pacific region. This research has shown that the US strategy to encounter the establishment of Asian Infrastructure Investment Bank (AIIB) by China is US should use economic strengthening strategy (Trans-Pacific Partnership) (TPP) for increasing trade volume between members and reducing trade volume against non member to balance of China influence in Aisa-Pacific region.